Pengaruh Pelatihan dan Kompensasi terhadap Kinerja Karyawan pada PT Nasional Perkasa Motor Ruteng - Rosalia H. Nono; Bonefasius Berdi; Marselina Ndahul (Universitas 45 Surabaya, 2025)
This study aims to determine the effect of job training and compensation on the performance of employees of PT Nasional Perkasa Motor Ruteng. This study used quantitative data. The data source in this study uses primary data by distributing questionnaires to employees of PT. National perkasa Motor Ruteng. The data source in this study uses primary data by distributing questionnaires to employees of PT. National Mighty Motor Ruteng. The population of this study is all employees of PT Nasional perkasa Motor Ruteng with a total of 45 employees. The sampling technique in this study used a saturated sample technique. Data analysis techniques in this study are multiple linear regression, instrument test, classical assumption test, and hypothesis test. The results showed that partial training had a significant effect on employee performance with a training t-count value of 4,128 greater than the t-table of 1,681 with a significance level of 0,000. Partially, compensation has an effect but not significant on performance with a compensation t-count value of 1.832 greater than the t-table of 1.681 with a significance level of 0.073. The independent variable consisting of training and compensation for variables tied to employee performance simultaneously has a value of 0.726 that the value of the coefficient of determination (R Square) is known to be 72.6%, this means that employee performance is influenced by training and compensation by 72.6% while the remaining 27.4% is influenced by other factors that are not studied. Training is the dominant variable in the performance of employees of PT Nasional Perkasa Motor Ruteng (Standardized Coefficient) of 0.611.